2012
DOI: 10.1007/s10857-012-9216-1
|View full text |Cite
|
Sign up to set email alerts
|

Professional mathematics teacher identity: analysis of reflective narratives from discourses and activities

Abstract: This article focuses on the methodological use of reflective narratives from discourses and activities of an experienced primary teacher as evidence of her professional identity. The teacher's reflective narratives emerge from her participation in a 3-year developmental and research project, Learning Communities in Mathematics, conducted at the University of Agder (UiA) in Norway. As background for our study, we firstly present the teacher in action with her sixth-grade pupils in a mathematics lesson, and then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 22 publications
(46 reference statements)
0
22
0
4
Order By: Relevance
“…Williams (2011) investigated how teachers draw on their past experiences (life histories) to develop role models that shape their identity. Other researchers have reported on how confidence (Graven 2004), emotion (Beauchamp and Thomas 2009), motivation (Gresalfi and Cobb 2012) and critical reflection (Beauchamp and Thomas 2009;Bjuland et al 2012;de Freitas 2008;Goodnough 2011) influence teacher identity. These, and the numerous other factors that influence teacher identity, do not act in isolation but are intimately connected; for example, lack of pedagogical content knowledge can influence confidence (Hobbs 2012) and professional learning can provide opportunities for increased critical reflection and confidence (Goodnough 2011).…”
Section: Developing a Conceptual Framework For Empirical Researchmentioning
confidence: 99%
“…Williams (2011) investigated how teachers draw on their past experiences (life histories) to develop role models that shape their identity. Other researchers have reported on how confidence (Graven 2004), emotion (Beauchamp and Thomas 2009), motivation (Gresalfi and Cobb 2012) and critical reflection (Beauchamp and Thomas 2009;Bjuland et al 2012;de Freitas 2008;Goodnough 2011) influence teacher identity. These, and the numerous other factors that influence teacher identity, do not act in isolation but are intimately connected; for example, lack of pedagogical content knowledge can influence confidence (Hobbs 2012) and professional learning can provide opportunities for increased critical reflection and confidence (Goodnough 2011).…”
Section: Developing a Conceptual Framework For Empirical Researchmentioning
confidence: 99%
“…Research on teachers' professional identity formation has expanded in recent years with the mutual goal to better understand and support the needs of teachers, including student teachers (Beijaard, Meijer & Verloop, 2004;Bjuland, Luiza Cestari & Borgersen 2012;Ponte & Chapman, 2008). The results presented in this paper derive from a longitudinal case study of seven novice primary school mathematics teachers' professional identity development (Palmér, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it could be argued that these factors, along with critical reflection, which is part of the action research process (McAteer, 2013), contributed to the development of the teachers' identities. The importance of critical reflection in shaping teacher identities was also evident in studies conducted by de Freitas (2008) and Bjuland et al, (2012). De Freitas used a narrative approach to investigate pre-service teachers' identity construction in relation to social justice issues, while Bjuland et al used reflective narratives as evidence of the teacher identity of a primary school teacher during a three-year research and development project.…”
Section: Identity and Teachersmentioning
confidence: 98%
“…However, this view contrasts with that of Sfard and Prusak (2005) who, while agreeing with Wenger that identities originate in practice, claimed that identity involves how these practices are seen and talked about rather than actual engagement in the practice. The narrative approach taken by Sfard and Prusak has shown promise in their research and that of others (e.g., Bjuland, Cestari, & Borgersen, 2012;Graven & Buytenhuys, 2011) and has similarities with the views of Wenger and Gee. However, teacher participation in practices which promote numeracy learning was an important aspect of the research reported on in this thesis, and so the conceptualisation of identity used in the present study is aligned with that of Wenger.…”
Section: Conceptualising Identitymentioning
confidence: 99%
See 1 more Smart Citation